Neutrophil Extracellular Trap Induced Dendritic Cell Activation Leads to Th1 Polarization in Type 1 Diabetes - Parackova, Zuzana; Zentsova, Irena; Vrabcova, Petra; Klocperk, Adam; Sumnik, Zdenek; Pruhova, Stepanka; Petruzelkova, Lenka; Hasler, Robert; Sediva, Anna (Frontiers in immunology, 2020)
Neutrophils releasing neutrophil extracellular traps (NETs) infiltrate the pancreas prior to type 1 diabetes (T1D) onset; however, the precise nature of their contribution to disease remains poorly defined. To examine how NETs affect immune functions in T1D, we investigated NET composition and their effect on dendritic cells (DCs) and T lymphocytes in T1D children. We showed that T1D patient NET composition differs substantially from that of healthy donors and that the presence of T1D-NETs in a mixed peripheral blood mononuclear cell culture caused a strong shift toward IFNγ-producing T lymphocytes, mediated through activation of innate immunity cells in T1D samples. Importantly, in a monocyte-derived DC (moDC) culture, NETs induced cytokine production, phenotypic change and IFNγ-producing T cells only in samples from T1D patients but not in those from healthy donors. RNA-seq analysis revealed that T1D-NETs presence causes TGFβ downregulation and IFNα upregulation and creates pro-T1D signature in healthy moDCs.
Keywords: innate immunity; Young Adult; Gene Expression Regulation; NET; type 1 diabetes; přirozená imunita; diabetes mellitus 1. typu; Male; monocyte-derived dendritic cells; Interferon-gamma; Transforming Growth Factor beta; mladý dospělý; Th1 buňky; Adolescent; Child; buněčná diferenciace; dítě; Adult; autoimmunity; interferon gama; dospělí; mužské pohlaví; Th1 Cells; dendritické buňky; Immunity, Innate; neutrofily; mladiství; transformující růstový faktor beta; kultivované buňky; lidé; ženské pohlaví; neutrophils; Humans; regulace genové exprese; netosis; extracelulární pasti; Neutrophils; rovnováha Th1-Th2; Cells, Cultured; Diabetes Mellitus, Type 1; Dendritic Cells; Extracellular Traps; Female; Th1-Th2 Balance; Cell Differentiation